Adverse events related to colonoscopy on the initial eleven years of a surgical team (Revista Argentina de Cirugía, 2021)
Background: colonoscopy is essential for the diagnosis and treatment of colorectal conditions, and is part of the surgeon’s resources. Complications associated with the procedure could be severe, and require an appropriate management.Objective: to analyze complications associated with colonoscopies done by a surgical team.Material and method: retrospective analysis on a prospective database. Diagnostic and therapeutic colonoscopies done by a surgical team between January 2005 and December 2016 were included. Complications and management strategies were analyzed. Results: of 3218 colonoscopies, 8 patients presented complications (0.2%). All were colon perforations solved by surgery, with primary closure and a kind of Hartmann’s procedure. There was no mortality In this series.Conclusions: although endoscopic procedures may have adverse effects, they can be done under standards of quality by surgeons. It is important that the intervening team be qualified for the solution of complications.
Keywords: digestive endoscopy; colonoscopy; surgeons; complication